2008
DOI: 10.4314/ari.v1i1.40739
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Fish Moisture Content On Oviposition, Fecundity And Development Of The Hide Beetle, Dermestes Maculatus Degeer (Coleoptera: Dermestidae)

Abstract: Oviposition, fecundity and development of Dermestes maculatus in Clarias ebriensis with different moisture contents (14%, 36%, 41%, 56%, 66%, 73%, 77%) were investigated from January to April, 2003. Catfish of different moisture content and a pair of male and female D. maculatus constituted a treatment and each of the seven treatments was replicated thrice. The treatment with fish of 14% moisture content served as the control. Generally, the pre-oviposition period, egg incubation period, oviposition peak, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
5
6
0
Order By: Relevance
“…The study revealed that in D. maculatus copulation occurred immediately the adults were paired and this could be explained as reported that both male and female D. maculatus produce sex pheromone (Rakoswki and Cymborowski, 1986;Jaskulska et al, 1987) which enhances communication and within 48 hours creamy white eggs were laid. The eggs laid were oval in shape and bluntly pointed at both ends as earlier reported (Archer and Elgar, 1999;Jones and Elgar, 2004;Ezenwaji and Obayi, 2004). The results of this study confirm the works of various researchers that D. maculatus females copulate within 30 minutes of pairing with the males initiating copulation (Archer and Elgar, 1999;Jones and Elgar, 2004).…”
Section: Oviposition In D Maculatus On Fish Substratessupporting
confidence: 90%
See 1 more Smart Citation
“…The study revealed that in D. maculatus copulation occurred immediately the adults were paired and this could be explained as reported that both male and female D. maculatus produce sex pheromone (Rakoswki and Cymborowski, 1986;Jaskulska et al, 1987) which enhances communication and within 48 hours creamy white eggs were laid. The eggs laid were oval in shape and bluntly pointed at both ends as earlier reported (Archer and Elgar, 1999;Jones and Elgar, 2004;Ezenwaji and Obayi, 2004). The results of this study confirm the works of various researchers that D. maculatus females copulate within 30 minutes of pairing with the males initiating copulation (Archer and Elgar, 1999;Jones and Elgar, 2004).…”
Section: Oviposition In D Maculatus On Fish Substratessupporting
confidence: 90%
“…Generally there was an initial increase in total number of eggs laid during the first week of oviposition on all the fish substrates but subsequently there was reduction in numbers as the days progressed and insects got older (Ezenwaji and Obayi, 2004). Oviposition behaviour in insects is an important contributor to the fitness of insects because of the consequent effect on the number and quality of offspring (Honek, 1993;Stejskal and Kucerova, 1996).…”
Section: Oviposition In D Maculatus On Fish Substratesmentioning
confidence: 99%
“…Females demonstrated a strong preference for ovipositing into the fur substrate as opposed to the paper or no cover situations, both in terms of the total number of progeny produced and in the rate of progeny per female. Though other studies have reported fresh or smoked fish as a diet and oviposition substrate for D. maculatus (Ezenwaji and Obayi, 2004;Zakka et al, 2013), this study used commercially available pet food as a diet with a separate oviposition substrate to facilitate the collection of individuals for bioassays. The advantages of using the dog food were that it is inexpensive, easy to obtain, does not have an objectionable odor and is shelf-stable.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that an increased moisture content shortened pre-oviposition and oviposition periods in females and increased the number of eggs compared with the 14% moisture control (Ezenwaji and Obayi, 2004). Moreover, Scoggin and Tauber (1951) reported a reduction in the number of larval instars and development period with increasing moisture content (up to 46%), though the sex ratio of adults reared on high moisture substrates was affected.…”
Section: Treatment Type and Position Of Furmentioning
confidence: 89%
“…For the purposes of the present study, in order to prevent fungus formation, the action of other contaminants, and the disguising of marks, the trotters had to be boiled and partially dehydrated. Furthermore, some reports have described skin beetles as consumers of partially wet tissue , whereas other authors performed heating treatments to disinfest tissue when carrying out experiments under controlled conditions .…”
Section: Discussionmentioning
confidence: 99%